The Anti-Phytophthora Effect of Selected Potato-Associated Pseudomonas Strains: From the Laboratory to the Field - Guyer, Anouk; De Vrieze, Mout; Bönisch, Denise; Gloor, Ramona; Musa, Tomke; Bodenhausen, Natacha; Bailly, Aurélien; Weisskopf, Laure (Frontiers in Microbiology, 2015)
Late blight, caused by the oomycete Phytophthora infestans, is the most devastating disease of potato. In organic farming, late Late blight, caused by the oomycete Phytophthora infestans, is the most devastating disease of potato. In organic farming, late blight is controlled by repeated applications of copper-based products, which negatively impact the environment. To find alternative solutions for late blight management, we have previously isolated a large collection of bacteria from the phyllosphere and the rhizosphere of potatoes. Here we report the antagonistic potential of these strains when co-cultivated with P. infestans as well as with other potato pathogens. We then focused on three Pseudomonas strains and compared their protective impact against late blight to that of well-known biocontrol strains in planta using a high-throughput leaf disc assay with automated picture analysis. When sprayed on the leaves of potatoes in the greenhouse, the strains were able to survive for at least 15 days. Under field conditions, populations decreased faster but all tested strains could still be retrieved after 8 days. The most active strain in vitro, P. chlororaphis R47, was also the best protectant on leaf discs from plants grown in the greenhouse experiment, but its protection potential could not be verified in the field due to unfavourable infection conditions. However, its protective effect against P. infestans in planta, its survival in the phyllosphere as well as its ability to colonise the potato rhizosphere in very high population densities, suggest a potential for field application, e.g. in the form of tuber treatment or leaf spray.